The Digital Divide in Fitness: AI Coaching vs. The Human Touch of Personal Trainers - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Digital Divide in Fitness: AI Coaching vs. The Human Touch of Personal Trainers The fitness industry is undergoing a profound transformation, driven...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Wearable Technology